Stanford University's Chinese-to-English Statistical Machine Translation System for the 2008 NIST Evaluation - Galley, Michel; Chang, Pi-Chuan; Cer, Daniel; Finkel, Jenny R.; Manning, Christopher D. (The 2008 NIST Open Machine Translation Evaluation Meeting, 2008)
This document describes Stanford University’s first entry into a NIST MT evaluation. Our entry to the 2008 evaluation mainly focused on establishing a competent baseline with a phrase-based system similar to (Och and Ney, 2004; Koehn et al., 2007).